Catla family production 2025 as part of the WorldFish Carp Genetic Improvement Program - Hamilton, Matthew (2025)
Generation 2 catla families produced in 2025 that survived to the time of hapa stocking. Families were produced as part of the WorldFish Carp Genetic Improvement Program.